2005
DOI: 10.1080/14992020500266803
|View full text |Cite
|
Sign up to set email alerts
|

The preferred response slopes and two-channel compression ratios in twenty listening conditions by hearing-impaired and normal-hearing listeners and their relationship to the acoustic input

Abstract: This paper presents the results from two experiments in which normal-hearing and hearing-impaired listeners used an adaptive procedure to select their preferred frequency response slope and two-channel compression ratios in twenty listening conditions. Whereas the preferred response slope mostly depended on the difference in SNR between frequency bands, the preferred output levels in two channels depended highly on the intensity level entering each band. In both cases, subjects preferred less gain in frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
7
33
1
Order By: Relevance
“…4B). This is in agreement with findings of Keidser et al (2005). Although there were no significant effects of controller on the selected slope (p ϭ 0.67), there was a moderately significant effect of controller on the selected overall gain (p ϭ 0.01).…”
Section: Preferred Responsessupporting
confidence: 93%
See 1 more Smart Citation
“…4B). This is in agreement with findings of Keidser et al (2005). Although there were no significant effects of controller on the selected slope (p ϭ 0.67), there was a moderately significant effect of controller on the selected overall gain (p ϭ 0.01).…”
Section: Preferred Responsessupporting
confidence: 93%
“…Another reason for the increase in hearing aid fitting complexity is that modern hearing aids allow activation of different processing strategies for different acoustical environments, as it is widely accepted that hearing aid users prefer different responses for different listening situations (Keidser, 1995;Keidser, et al, 2005). Unlike the gain-frequency response of a hearing aid, which is traditionally determined by an individual's audiometric data, it has been suggested that modern hearing aid features should be fitted according to the characteristics of the acoustic environment (Kiessling, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…The smaller the dynamic range of hearing is at a given frequency, the higher a CR would be needed to make all speech sounds audible. However, applying compression to the rapidly fluctuating speech signal causes some level of distortion to both the spectral and temporal cues (e.g., Bustamante & Braida, 1987;Moore, 1990;Plomp, 1988), and several studies suggest that for people with mild or moderate hearing loss such distortions have a deleterious effect on speech discrimination, or diminish ratings of sound quality and preference, when using CRs much greater than 3:1 in conjunction with fast time constants and multiple channels (Keidser et al, 2005a;Neuman, Bakke, Mackersie, Hellman, & Levitt, 1998;Plomp, 1994;Verschuure, Prinsen, Dreschler, 1994). Therefore, a compromise between audibility and acceptable sound quality and optimum speech understanding seems inevitable.…”
Section: Compression Limit For Fast-acting Compressionmentioning
confidence: 99%
“…Various prescription methods result in prescription targets that differ from individually preferred gain by up to 10 dB or more, particularly at the high frequencies Keidser et al, 2005;Keidser, O'Brien, Carter, McLelland, & Yeend, 2008;Mueller, 2005;Polonenko, Scollie, & Moodie, 2010;Smeds et al, 2006;Zakis, Dillon, & McDermott, 2007). Other studies have reported that mean preferred overall gain is about 3 to 4 dB less than the prescriptive targets Horwitz & Turner, 1997;Humes, Wilson, Barlow, & Garner, 2002;Keidser, O'Brien, et al, 2008;Marriage et al, 2004;Mueller & Bentler, 2005;Polonenko et al, 2010;Zakis et al, 2007).…”
Section: Pico Question Nomentioning
confidence: 99%
“…In a laboratory experiment, Keidser et al (2005) found that less gain is preferred in frequency bands where noise is more annoying and the preferred frequency response slopes depend on the slope of the audiogram. Convery et al (2005), Keidser, Dillon, et al (2008) and Smeds et al (2006) also found that the preferred gain-frequency response varied with listening conditions.…”
Section: Pico Question Nomentioning
confidence: 99%